Influence of surfactants on the in-vitro release and permeation of lorazepam from tablets - Singh J.; Singh S. (My University, 2025)
Sodium lauryl sulfate, tween 80, sodium taurocholate and sodium tauroglycocholate were included into lorazepam tablet formulations to increase the dissolution and permeation of the drug. The increasing concentration of the surfactants has increased the dissolution and permeation of the drug. The fractional quantity remained to be permeated versus time plots show the exponential decay. © 1990 Informa UK Ltd All rights reserved: reproduction in whole or part not permitted.